Digital Transformation in Higher Education – A Study on Productivity and Environmental Sustainability - Muthu, Catherine; Chen, Sze Liang; Khoo, Wen Hui (INTI International University, 2023)
Tertiary education is essential as it helps to boost economic growth, reduce poverty, and promote shared prosperity, leading to a higher demand for higher education worldwide. International business promotes not only the exchange of goods and services but also the transfer of resources, ideas, and people. As a result, tertiary education institutions are expanding their abroad programmes in order to attract students interested in international education. However, the unprecedented outbreak of COVID-19 has strongly affected tertiary education, as most countries have implemented travel restrictions and prohibited people from entering or leaving. Therefore, online learning was implemented worldwide in order to overcome the challenges. Nonetheless, students are able to attend classes at any location as long as they have a stable internet connection. In addition, the concept of online learning reduces the time and travel costs for students to attend physical classes. Moreover, online lectures are able to be recorded, allowing students to review and revise previous lectures they would have missed. However, there are challenges to online learning, such as a lack of motivation and interaction between students and lecturers, poor teaching quality due to a lack of technical skills, and students who are easily distracted. This study will examine the adoption of online platforms for teaching and learning in the higher education industry and its prospects for higher productivity and a positive impact on environmental sustainability.